Kondisi makroekonomi dan kinerja perbankan di Indonesia - Febriana Mk, Irma; Herlina Sitorus, Nurbetty; Malia, Rizka (Jurnal Paradigma Ekonomika, 2021)
The purpose of this study was to see how the long-term and short-term relationship between banking performance and macroeconomic variables. The analysis method used is the vector error correction model (VECM) with the variables ROA, BOPO, LDR, industrial production index, CPI, and BI rate. The results of this study indicate that there is a significant positive relationship between ROA and industrial production index in the long run and a significant negative relationship between ROA and CPI in the long and short term. There is a significant negative relationship between BOPO and the industrial production index in the long and short term. LDR has a significant negative relationship with all macro variables in the long term whereas, in the short term, LDR has a significant negative relationship with the CPI. Â